Crisis management : resilience and change - Kovoor-Misra, Sarah (Los Angeles, CA : SAGE Publications, Inc., 2020)
KEY FEATURES: This innovative text takes a transformative approach, emphasizing how organizations can seek to be excellent, learn and build organizational capacity, maintain trust and goodwill of their key stakeholders, and rebuild after crises. A chapter on transformative leaders underscores the crucial role of leadership, mindset, and values. Real-world cases analyze the cause and impact of crises at organizations including Apple, Uber, SpaceX, and Wells Fargo, keeping readers on the front line of the field. Case Analysis boxes feature questions designed for students to directly apply knowledge learned from the text to real-world situations. Global Insight boxes examine cultural differences around the world and how they impact managerial decisions during trying times. Ethical Insight boxes highlight the importance of moral ownership and courage during crises. Self Organizational Assessments and Experiential Exercises encourage readers to apply knowledge to one's own context and experience. Interwoven discussions of how modern technologies are changing the business landscape demonstrate how organizations are working to remain competitive and maintain the trust of their stakeholders.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Crisis management